The Influence of Halal Literacy on Purchasing Decisions of Wardah Products in Banda Aceh City - Murni, Seri; Humaira, Humaira Aprilia Yusra (Program Studi Perbankan Syariah FEBIII UIN Ar-Raniry, 2026)
In this era of globalization, many cosmetic products have emerged whose halal status is unknown. Therefore, it is important to conduct research on halal cosmetic products because halal literacy is still low. This study aims to determine the effect of halal literacy on purchasing decisions for Wardah products in Banda Aceh City. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to consumers who use Wardah products. The sampling method used in this study is probability sampling. Simple random sampling, a probability sampling approach, was applied in this study with a sample size of 100 respondents. The analysis technique used in this study is simple linear regression with the help of SPSS software version 25. The results of this study indicate that halal literacy has a significant influence on purchasing decisions for Wardah products in Banda Aceh City by 0.466 or 46.6%. The higher the consumer's halal literacy, the more likely they are to choose products that meet halal standards.